2015
DOI: 10.1158/1538-7445.am2015-3346
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3346: The ketone body β-hydroxybutyrate increases radiosensitivity in glioma cell lines in vitro

Abstract: Glioblastoma (GB) is the most common and aggressive primary malignant brain tumor. Despite aggressive treatment, including maximum surgical resection followed by both chemotherapy and radiotherapy, median survival for patients remains at approximately 1.5 years after diagnosis. Recent preclinical studies examining the potential of the ketogenic diet (KD) as an adjuvant therapy for the treatment of malignant gliomas demonstrated that animals fed a KD and treated with chemotherapy or radiation survived significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Indeed, preliminary studies have demonstrated that the KD enhances OxS-mediated radiation-induced DNA damage in glioma, but reduces it in surrounding healthy tissue [58]. However, Scheck and colleagues recently presented findings that βHB itself potentiates radiation therapy and increases radiosensitivity of glioma cells in vitro, regardless of glucose concentration [121]. A reduction in c-Myc expression, an oncogene known to play a vital role in DNA repair, was also observed thus suggesting ketone-enhancement of radiotherapy may be mediated via a signaling mechanism [116].…”
Section: Modulation Of Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, preliminary studies have demonstrated that the KD enhances OxS-mediated radiation-induced DNA damage in glioma, but reduces it in surrounding healthy tissue [58]. However, Scheck and colleagues recently presented findings that βHB itself potentiates radiation therapy and increases radiosensitivity of glioma cells in vitro, regardless of glucose concentration [121]. A reduction in c-Myc expression, an oncogene known to play a vital role in DNA repair, was also observed thus suggesting ketone-enhancement of radiotherapy may be mediated via a signaling mechanism [116].…”
Section: Modulation Of Oxidative Stressmentioning
confidence: 99%
“…Scheck and colleagues reported in a series of studies that the KD fed ad libitum increases median survival time by approximately 20-30% in the GL-261 malignant glioma model [63,117,121]. Poff et al reported that two KDs tested prolonged survival time by approximately 45% and 55% in a glioma-derived mouse model of metastatic cancer [12,126].…”
Section: Preclinical Evidence Demonstrating the Effectiveness Of Kd In Treating Gliomasmentioning
confidence: 99%
“…In vitro investigations demonstrated that βHB is able to recapitulate, in part, the in vivo effects of the full KD (Skinner et al, 2009; Rossi et al, 2015). This suggests that the ketone bodies themselves possess antitumor effects, and that perhaps the effects of the KD are mediated, at least in part, by the ketone bodies.…”
Section: β-Hydroxybutyrate As An Anti-cancer Agentmentioning
confidence: 99%
“…In vitro studies using βHB demonstrated that, even in the presence of high glucose, physiologically relevant doses of βHB reduced proliferation of several human glioblastoma cell lines, two human cancer stem cell lines, and a murine glioma cell line. Additionally, similar treatment with βHB resulted in potentiation of low doses of ionizing radiation therapy in both sensitive and resistant populations (Rossi et al, 2015; Silva-Nichols et al, 2015). Further, in a separate study βHB potentiated the chemotherapeutic agent 1,3-bis(2-chloroethyl)-1 nitrosourea (BCNU, carmustine) in a cell line derived from a recurrent human glioblastoma (Scheck et al, 2012).…”
Section: β-Hydroxybutyrate As An Anti-cancer Agentmentioning
confidence: 99%
“…This heightened glycolytic activity stimulates the pentose phosphate pathway, generating two molecules of nicotinamide adenine dinucleotide phosphate (NADPH), which are crucial for mitigating oxidative stress within cancer cells [40]. Physiologically relevant doses of β-HB effectively restrained the growth of various human glioblastoma cell lines and a murine glioma cell line in vitro, despite high glucose levels, as demonstrated by earlier studies [41,42]. In our study, the levels of β-HB were increased using IF (Figure 5).…”
Section: Discussionmentioning
confidence: 73%